RISK ANALYSIS FOR IRAQ, 2023. A VIEWPOINT - Stefan VLADUTESCU (Social Sciences and Education Research Review)
The present study is limited to efforts to clarify the articulations of risk analysis and to illustrate the fact that the most important element of risk analysis is the identification of risk factors and the identification of their influence on the development of economic, political, social and climatic processes. The risk situation in a country with a difficult to predict future like Iraq is approached as a case study.